2005
DOI: 10.1111/j.1600-051x.2005.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non‐surgical periodontal treatment with or without doxycycline on the periodontium of type 1 diabetic patients

Abstract: Although both periodontal treatment regimens are effective in type 1 diabetics, the use of doxycycline as an adjunct, provided more significant results when good plaque control was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
6
54
1
Order By: Relevance
“…Mean PPD and mean CAL is a continuous variable to evaluate periodontal disease severity (22), other authors have used discontinuous variables classifying this disease in low threshold periodontitis (mild periodontal disease) and high threshold periodontitis (advanced disease) (23). Mean PPD and mean CAL are a pretty accurate ways of evaluating periodontal disease severity and these values were correlated with hs-CRP levels to find any relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Mean PPD and mean CAL is a continuous variable to evaluate periodontal disease severity (22), other authors have used discontinuous variables classifying this disease in low threshold periodontitis (mild periodontal disease) and high threshold periodontitis (advanced disease) (23). Mean PPD and mean CAL are a pretty accurate ways of evaluating periodontal disease severity and these values were correlated with hs-CRP levels to find any relationship.…”
Section: Discussionmentioning
confidence: 99%
“…96 Doxycycline, a broad-spectrum antimicrobial agent, is a tetracycline derivative which has been The properties of doxycycline seem to be useful in periodontal therapy because of its antibacterial, anti-collagenolytic, anti-inflammatory effects, and fibroblast-stimulating activities. 106,107 Doxycycline was able to inhibit in vitro osteoclastogenesis and cause apoptosis of mature osteoclasts due to bone resorption. These effects extend beyond the mere inhibition of MMP.…”
Section: Doxycyclinesmentioning
confidence: 99%
“…Moreover, administration of doxycycline additional to periodontal therapy has the potential to alter diabetes metabolic control. 107,121,122 Also it has stated that doxycycline inhibits non-enzymatic glycation of extracellular proteins, and it may have a similar effect on the glycation of hemoglobin. 123 Several studies suggest that the administration of systemic doxycycline can result in improvement of metabolic control especially in poorly controlled type 2 DM periodontitis patients.…”
Section: The Use Of Doxycycline In Diabetes Mellitus With Periodontalmentioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60] Furthermore, reports show that use of systemic antibiotics as an adjunct to SRP may be more beneficial for diabetic patients. Two studies reported that use of systemic doxycycline 100 mg for two weeks provided better reductions in PD, 61,62 Porphyromonas gingivalis, and glycated hemoglobin (HbA 1c ) levels. 61 when compared with diabetics receiving mechanical therapy alone.…”
mentioning
confidence: 99%